Physiotherapy assessment and diagnosis of musculoskeletal disorders of the knee via telerehabilitation - Richardson, Bradley R; Truter, Piers; Blumke, Robert; Russell, Trevor G (Journal of telemedicine and telecare, 2017)
Introduction Lower limb musculoskeletal disorders place a heavy burden on healthcare systems. Appropriate management of these conditions is critical, however access to appropriate physiotherapy services is difficult for those in geographically remote areas or those with mobility or transport difficulties. The aim of this study was to evaluate the accuracy and reliability of an online musculoskeletal physiotherapy assessment of the knee complex using telerehabilitation compared to traditional face-to-face assessment. Methods In a repeated-measures design, 18 subjects who sought treatment for knee pain underwent a traditional face-to-face assessment and a remote telerehabilitation assessment. Telerehabilitation assessments were conducted with participants performing facilitated self-palpation, self-applied modified orthopaedic tests, active movements and functional tasks. Results Primary pathoanatomical diagnoses were in exact agreement in 67% of cases and were similar in 89% of cases. The system of pathology was found to be in agreement in 17 out of 18 cases (94%). Comparisons of objective findings from the two physical assessments demonstrated substantial agreement (kappa = 0.635) for categorical data and binary data (chi-squared = 400.36; p < 0.001). A high level of intra-rater (89%) and moderate level of inter-rater (67%) reliability was evident for telerehabilitation assessments. Discussion Telerehabilitation assessment of the knee complex appears to be feasible and reliable. This study has implications for clinical practice and the development of physiotherapy services to address the burden of lower limb musculoskeletal pain and disability.